Self-assembled monolayer of Au nanodots deposited on porous semiconductor structures - Tiginyanu, Ion; Monaico, Eduard; Nielsch, Kornelius (ECS Electrochemistry Letters, 2015)
We demonstrate the possibility to cover the surface of GaP and InP porous structures by a self-assembled monolayer of electrochemically deposited nanoscale Au nanodots. After nucleation, each dot was found to increase in sizes up to a critical transverse dimension, the process of pulsed electrodeposition of gold being continuously supported by the formation of new nanodots. The density of deposited Au dots is shown to be dependent upon the number and width of the applied voltage pulses. The deposition of "size-saturated" dots continues until the entire surface exposed to the electrolyte is covered by a monolayer of self-assembled Au nanodots.
CRIS-Team Scopus Importer:2023-03-20